Bone Loss in Diabetes Mellitus Diaporosis - Kupai Krisztina (INTERNATIONAL JOURNAL OF MOLECULAR SCIENCES, 2024)
The objective of this review is to examine the connection between osteoporosis and diabetes, compare the underlying causes of osteoporosis in various forms of diabetes, and suggest optimal methods for diagnosing and assessing fracture risk in diabetic patients. This narrative review discusses the key factors contributing to the heightened risk of fractures in individuals with diabetes, as well as the shared elements impacting the treatment of both diabetes mellitus and osteoporosis. Understanding the close link between diabetes and a heightened risk of fractures is crucial in effectively managing both conditions. There are several review articles of meta-analysis regarding diaporosis. Nevertheless, no review articles showed collected and well-organized medications of antidiabetics and made for inconvenient reading for those who were interested in details of drug mechanisms. In this article, we presented collected and comprehensive charts of every antidiabetic medication which was linked to fracture risk and indicated plausible descriptions according to research articles.